Effect of Additional Variations Hydroxyl Propyl Methyl Cellulose (HPMC) on Making of Patchouli Waxing Gel - Kamaruzzaman, Suraiya; Asri, Syilviana; Putri, Azzahra Iskandar; Fakhirah, Cut Syafanah; Fahira, Dhea; Novela, Yaza (Journal of Patchouli and Essential Oil Products, 2023)
Waxing gel is included in cosmetic epilation which can damage the skin barrier. To overcome this, it is necessary to add a composition that can moisturize, prevent irritation, and maximize its lifting power. In minimizing the possibility of irritation, it is necessary to add allantoin to waxing preparations as a calming agent that is safe for sensitive skin. The purpose of this study was to determine the effect of the of Hydroxyl Propyl Methyl Cellulose (HPMC) on the resulting waxing gel preparation including aroma, thickness, and maximum hair lift in certain areas of the body and to determine the best HPMC for removing unwanted hair. This type of research is experimental research with independent variables, namely HPMC variations of 0%, 1%, 2%, 3%, and 4%. The research procedure consists of preparation of tools, preparation of raw materials, and products produced. After that, several panelists made observations by giving questionnaires regarding aroma, viscosity and lifting power. The results showed that there was a comparative effect of the HPMC s used. Based on the observations of several panelists on the aroma, thickness, and lifting power of the waxing gel that has been made, it is known that at the HPMC 0% and 1% HPMC variables, it was found that many panelists stated that the waxing gel in these variables had a fragrant aroma, had a very rich texture. viscous and has very good lifting power compared to waxing gel variables , namely 2% HPMC, 3% HPMC, and 4%.